Bahasa IMPLEMENTASI PROGRAM INVENTARISASI PENGUASAAN PEMILIKAN PENGGUNAAN DAN PEMANFAATAN TANAH (IP4T) PARTISIPATIF DI DESA KEDUNGREJO KECAMATAN PILANGKENCENG KABUPATEN MADIUNIndonesia - Lusy Riadina Putri (Jurnal Kebijakan Pemerintahan, 2020)
In order to realize the landreform in Indonesia at this time, National Land Agency/BPN Implement the IP4T Program (lnventarity Mastery, ownership, use and utilization land) which was then developed by BPN District Madiun and Regional Leadership Communication Forum/FORKOPIMDA Madiun Regency into a IP4T Participative Program. This activity is intended as a database of land areas and the synchronization of agricultural activities by involving other supporting elements such as Local Government of Madiun Regency, The Army Force, and The Police.The research methods are used through qualitative approaches with descriptive types. Data sources come from documents and informant. Data collection techniques are conducted through observation, interviews and documentation. The Data is analyzed by using SWOT analysis to provide priority implementation of alternative strategies produced.The result of this research are good to implementation of participatory IP4T Program in Kedungrejo village in Pilangkenceng subdistrict Madiun Regency, but there are constraints such as the movement of community participation is less evenly, limitation of technical equipment and operational problems of the absence of village boundary patok with Forest, lack of public knowledge about the regulations of the main procedures and ordinances of land registration.Strategies that can be done to effectively implement IP4T participatory Program with monitoring of the program in each stage process, holding a joint coordination with the Perhutani to determine the boundary between the Village with Forest, persuasive socialization by means of house to house so that the community as a target program can easily understand the purpose and objectives of the participatory IP4T Program.Keywords: Implementation, IP4T Participatory Program, and Land.